PILOT PROJECTS IN THE PROVISION OF ADMINISTRATIVE SERVICES IN THE FIELD OF JUSTICE (ON THE EXAMPLE OF THE PILOT PROJECT “MARRIAGE IN 24 HOURS”) - Yushchenko , M. (Theory and Practice of Public Administration, 2020)
The purpose of the article is to study the provision of administrative services in the field of registration of civil status during the implementation of the pilot project “Marriage in 24 hours”. The essence of the study. The pilot project “State registration of marriage in 24 hours” provides the possibility of state registration of marriage in the place and within the period specified by the applicant, including the day of submission of the application. The city of Odessa, one of the first cities in Ukraine, on July 31, 2016 began to provide such a service, which is in great demand among the population. This service can be obtained in all regions of our country, which was introduced during 2017 and 2018. For three and a half years, 92 133 couples have used the service of state registration of marriage in a short time, which was called “Marriage in 24 hours”. The number of marriage records in which there is a mark of divorce - 3770. Due to the fact that the number of registrations of marriages with foreign nationals is more than 30% of registrations, it is believed that this project has made it possible to legalize foreign nationals in a short time, which increased the registration of sham marriages. In this regard, clear regulation of marriage with foreigners in Ukraine is extremely important. More than 100 legal entities throughout the country provide services for the organization of state registration of marriage at a cost that is high for the average citizen. In addition, newlyweds need to pay for the services to the department of state registration of civil status, which carries out the state registration of marriage. In general, such a service for the registration of marriage in a short time costs from 3 000 UAH. up to UAH 10 000, in each region differently. It does not meet the key characteristics of the service state. Indicators show how effective and justified the new procedure for quick marriage registration turned out to be. The state budget received UAH 178 262 819 for the provision of such a service. Odessa is the only city in Ukraine where such a service was provided round the clock by the State Enterprise “Citizen Service Center”, so during this period 13 450 marriages were registered and paid services were provided in the amount of UAH 21 794 856. The amount of payment for this service is high for most citizens of our country, which is in a state of war and economic crisis now. Unfortunately the payment for this service is different in each region. Therefore, it is extremely important to adopt a law on administrative fees, which will regulate the issue of payment for marriage registration throughout Ukraine. It should be noted that the introduction of the pilot project “Marriage in 24 hours” in July 2016 was extremely important, but it gave the opportunity to increase the number of sham marriages and eliminate the institution of the family. Having analyzed the quality and accessibility of the Pilot Project “Marriage in 24 hours”, it can be safely called “successful business project”, but not available to many citizens of our country, thereby violating their rights. We believe that the high cost of this service contributes to the violation of equality between citizens who will not be able to use the services through financial insolvency. We identify both the advantages and disadvantages of the project of reduction in time of marriage registration, the time factor: the groom and the bride do not have to wait several months, but the marriage is contracted this way, may be hasty and it does not strengthen the family. Currently, the protection of human and civil rights in the context of the application of legal norms on registration of civil status and the need to adopt a new version of the law on civil registration, which will provide an opportunity within a reasonable time, at the citizen’s choice and at a convenient time and place, free of charge or with a modest fee to carry out the state registration of the civil status act, is most timely.